Strategi Sanggar Tari Aulia dalam Personal Branding di Media Sosial - Jannati, Zhila; Apriko, M. Syendi; Puspita, Mila (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
Social media has become a strategic space for artists to build their image and expand their audience reach in the digital era. This study analyzes the personal branding strategies implemented by the Aulia Dance Studio in Palembang through Instagram and TikTok. The focus of the research is directed at how the studio owner constructs elements of identity, consistency, and relevance in representing cultural values ​​in the digital space. This study uses a descriptive qualitative method with data collection techniques such as in-depth interviews and content analysis of purposively selected social media posts. The results show that the Aulia Dance Studio's personal branding is built through a consistent cultural visual identity and adaptation to digital trends without eliminating traditional values. These findings strengthen the perspective that culture-based personal branding can be an effective cultural da'wah strategy on social media.